Induction of periodontal disease via retentive ligature, lipopolysaccharide injection and their combination in a rat model - Mustafa, Hana Hassan (2018)
Periodontitis is a highly prevalent, chronic immune-inflammatory disease of the periodontium that results in progressive degradation of the periodontium and alveolar bone loss. This thesis aims to evaluate the induction of periodontal disease via retentive ligature, lipopolysaccharide, and their combination in a rat model. Seventy two Sprague Dawley rats were distributed into four treatment groups: 1) control group with no treatment; 2) application of 4/0 nylon ligature around 2nd maxillary molars; 3) intragingival injection of Porphyromonas gingivalis lipopolysaccharide (LPS) to the palatal mucosa of the 2nd maxilla molars; 4) combination of ligature and LPS injection (ligature-LPS). At 7, 14, 30 days after the induction of periodontal disease, 6 rats of each group were sacrificed. Morphological changes in the gingival tissues were evaluated according to Loe & Sillness Gingival Index and Plaque Index. Alveolar bone loss were evaluated histologically and via microcomputed tomography. Parametric data were analysed using two-way ANOVA followed by Tukey test with significance set at 5%. Non-parametric data were analysed using Kruskal-Wallis followed by multiple comparisons with Bonferroni’s correction. The morphological, histological and radiological results revealed significant degenerative changes in the periodontal tissues and alveolar bone following both the ligature and ligature-LPS induction techniques. These changes were evident as early as 7 days; maintained until 14 days, and declined with time. There was minimal difference in the changes induced by ligature-LPS when compared to ligature alone. Injection with LPS alone resulted in minimal increase of the Gingival and Plaque Index, and insignificant histological and radiological changes when compared to the controls. In conclusions, the ligature technique was effective to induce acute periodontal disease. The LPS injection technique in this study was not effective to induce alveolar bone loss, and its combination to ligature added insignificant effect.